Correlation between BAL CXCR3 chemokines and lung allograft histopathologies: A multicenter study. Issue 10 (16th June 2021) - Shino, Michael Y.; Li, Ning; Todd, Jamie L.; Neely, Megan L.; Kirchner, Jerry; Kopetskie, Heather; Sever, Michelle L.; Frankel, Courtney W.; Snyder, Laurie D.; Pavlisko, Elizabeth N.; Martinu, Tereza; Singer, Lianne G.; et al.
Abstract : The histopathologic diagnosis of acute allograft injury is prognostically important in lung transplantation with evidence demonstrating a strong and consistent association between acute rejection (AR), acute lung injury (ALI), and the subsequent development of chronic lung allograft dysfunction (CLAD). The pathogenesis of these allograft injuries, however, remains poorly understood. CXCL9 and CXCL10 are CXC chemokines induced by interferon‐γ and act as potent chemoattractants of mononuclear cells. We hypothesized that these chemokines are involved in the mononuclear cell recruitment associated with AR and ALI. We further hypothesized that the increased activity of these chemokines could be quantified as increased levels in the bronchoalveolar lavage fluid. In this prospective multicenter study, we evaluate the incidence of histopathologic allograft injury development during the first‐year post‐transplant and measure bronchoalveolar CXCL9 and CXCL10 levels at the time of the biopsy. In multivariable models, CXCL9 levels were 1.7‐fold and 2.1‐fold higher during AR and ALI compared with "normal" biopsies without histopathology. Similarly, CXCL10 levels were 1.6‐fold and 2.2‐fold higher during these histopathologies, respectively. These findings support the association of CXCL9 and CXCL10 with episodes of AR and ALI and provide potential insight into the pathogenesis of these deleterious events. Abstract : This prospective multicenter study evaluating the incidence of allograft histopathology during the first year after lung transplantation finds that CXCL9 and CXCL10 are elevated in bronchoalveolar lavage specimens during acute rejection and acute lung injury, two major risk factors for chronic lung allograft dysfunction.